Carotid Doppler Study in Patients with Cerebral Infarction - Ahmed, Laith; Abdullah Noori, Firas (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Duplex ultrasound is inexpensive, non-invasive and can provide functional and anatomical information about vessel stenosis and plaque morphology. Color duplex flow ultrasonography has thus become the most widely used noninvasive method of assessing extra cranial cerebrovascular occlusive disease.Objectives:To find the relation of the severity of carotid artery stenosis, intima media thickness, and atheromatous plaque morphology with the size of cerebral infarction.Patients and Methods: A prospective study, conducted from September 2010 to May 2011, in Department of Radiology in Baghdad Teaching Hospital. A total of 62 Patients with clinical & radiological (brain CT) diagnosis of acute stroke, (42 males & 20 females) had been referred from Medical & Neurological units to the Radiology Department / Ultrasound Unit for carotid arteries examination.Results: Thirty out of 62(48.4%) patients had evidence of ipsilateral carotid stenosis distributed as: 18 out of 30 patients (60%) had < 50% stenosis, 8 patients (26.7%) had 50-69% stenosis, and 4 patients (13.3%) had > 70% stenosis. Also in our study we found that homogenous hypoechoic and ulcerated plaques were more frequent in patients with large size infarcts.Conclusion: From this study we concluded that the size of cerebral infarction is related to degree of ipsilateral carotid artery stenosis, especially when the plaque is soft with irregular or ulcerated surface, and that increased intima media thickness of common carotid artery is strongly associated with stroke and its risk factors.